Cloud Applications Management – Issues and Developments - Odun-Ayo, I.; Odede, B.; Ahuja, R. (Computational Science and Its Applications - ICCSA 2018, 2018)
Cloud computing is a platform that dictates the mode of operations within most data centers. Cloud computing relieves its consumer’s from investment in IT infrastructure. Cloud consumers are provided with on-demand services at affordable cost. Cloud service providers offer custom made applications that can be used by a variety of users to handle routine tasks. Cloud service providers also offer their users programming interfaces that enables developers design and deploy applications efficiently. In addition, it is very important for cloud service providers to regulate resources based on the workload on the applications and provide computational resources and storage. Despite cloud computing benefits, it is difficult for cloud users to port applications from one platform to another, this difficulty is inevitable because of the cost and complexity of porting such applications. In addition, it is essential for the cloud service providers to adjust resources based on workloads or failures on the system. This paper discusses key concepts of cloud applications management, issues and development and also reviews recent related literature on cloud application management. This paper examines present trends in the area of cloud application management and provides a guide for future research. In this paper, the main objective is to answer the following questions: what is the current development and trend in cloud application management? Papers published in journals, conferences and white papers were analyzed. The result in this review shows that there is insufficient discussion in the area of trust management and security as it relates to cloud applications management. This would be beneficial to prospective cloud users, researchers and cloud service providers alike.